Design and characterization of the 2DoF Drone: a multirotor platform for education and research. Issue 12 (2021) - Panza, Simone; Invernizzi, Davide; Giurato, Mattia; Lovera, Marco
Abstract: In this paper we present the design of a laboratory test-bed for education and research which is intended to replicate the dynamic behavior and the control design challenges of an underactuated multirotor Unmanned Aerial Vehicle (UAV). The proposed setup is designed to study the longitudinal and pitch dynamics of a multirotor UAV by running experiments in a safe and controlled environment and in a repeatable way. Based on an open-source firmware (PX4), customizable by the user for advanced research implementations, a dedicated software has been developed to implement controllers at high level in Simulink, to automatically generate and integrate the controller code into the firmware and then to command the drone from MATLAB. In view of remote teaching activities, the setup hardware and software allows for an easy remote access that still provides a satisfactory learning experience to the users. Physically motivated identification procedures have been devised to characterize the platform dynamics for didactic purposes and for the use in the design of control laws.